Eksistensi lembaga hisbah modern di Indonesia - Rochimah, Ainun (Maliki Interdisciplinary Journal, 2024)
The modern business world, which should provide many benefits to business people and consumers, is inseparable from deviations that are detrimental to other parties. Islam orders Muslims to oversee business activities so that they can run according to Islamic sharia. Hisbah or supervision is carried out with the principle of amar ma'ruf nahy munkar. Indonesia mobilizes hisbah or supervisory institutions to take action on irregularities that occur in business activities. This supervision is carried out through institutions such as KPPU, BPKN, BPOM, DSN, OJK, and Wilayatul Hisbah. The existence of hisbah institutions in Indonesia can guide business activities according to Islamic sharia, by not committing deviations for the sake of seeking personal gain.